Thermal non-equilibrium simulation of diffuse and constricted anode attachments of a high intensity transferred arc. (6th July 2022) - Niu, Chong; Geng, Jin-Yue; Sun, Su-Rong; Shen, Yan; Zhu, Tao; Wang, Hai-Xing
The arc attachment modes on anode of a high intensity argon arc with water-cooled constrictor are numerically investigated by a two-temperature model. An inelastic electron energy loss factor, representing the energy loss due to non-equilibrium chemical kinetic processes, is introduced to the electron energy equation. Two different attachment modes, i.e., diffuse and constricted anode attachments, are obtained based on the experimental conditions. Results for both anode attachment modes indicate that the temperature discrepancy between electrons and heavy particles is very pronounced in the arc fringes and in the regions close to the anode. By comparing the axial and radial Lorentz forces between the diffuse and constricted anode attachments, it is found that the larger axial and radial Lorentz forces in a constricted anode attachment are the main cause for the formation and maintenance of anode jet. The effects of inelastic electron energy loss on different anode attachment modes are discussed and the results indicate that it is very important to consider the chemical non-equilibrium processes in an appropriate way for predicting arc attachment modes on anode reasonably.